SISTEM INFORMASI MEDIA PROMOSI DAN PEMBELAJARAN KELOMPOK TARUNA TANI AULIA - Indrawan, Rama; Agitha, Nadiyasari; Ratnasari, Dwi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2024)
This research focuses on the challenges faced by the Taruna Tani Aulia group in educating farmers about the transition from chemical fertilizers to organic fertilizers. Many farmers find the process of producing organic fertilizers complex and time-consuming, making them reluctant to switch. To address this issue, this study developed an information system that serves as both a promotional tool and a learning platform, facilitating the dissemination of information on the benefits of organic fertilizers and promoting organic fertilizer products sold by Taruna Tani Aulia. The system was developed using the Prototyping Method, allowing for iterative testing and evaluation with direct user feedback. The system was built using the Next.js framework to streamline the development process. The results of testing using the Mean Opinion Score indicated a high level of user acceptance, with a User Acceptance Test score of 87.8%. This suggests that the system is feasible and effective in supporting the promotion and education of organic fertilizers. In conclusion, this information system can help farmers more easily understand and adopt organic farming practices, as well as simplify their access to purchasing organic fertilizers without the need to produce them independently.